Do altar para o palco: os shows em movimento do Padre Fábio de Melo. - Pessoa, Silvério Leal (2019)
This thesis describes contemporary Catholic music from the production of the symbolic goods offered by Father Fábio de Melo with emphasis on the shows as re-significances of new practices in the Brazilian Catholic field based on co-relations and adhesions of the logics and meanings of the field of industry cultural. The research is based on the premise that the artistic production of the agent mentioned is linked to the new dynamics in the Catholic field, including the inspiration of the new communities linked to the Charismatic Renewal. The show and music receive new senses and representations marked by religious practices based on emotion, festive and spectacular character. In order to corroborate this thesis that shows an intense movement involving the concerts, the artists of the faith and a process between fields, the Catholic and the cultural industry, it will be analyzed the agent's performances, his musical reflections and the amplification of social networks widely used by the Catholic denomination. The study will be based on a reconstruction of the senses of the Catholic fields and the cultural industry, underlining the emergence and consolidation of new dynamics and agents, under which emerges the artistic production of Father Fábio. The research will use the following procedures for data collection: documentary research, interviews and participant observation. From the theoretical-methodological point of view, the concepts of deinstitutionalization of Danièle Herviu-Léger will be adopted; field, capital, property, and symbolic capital from Pierre Bourdieu; television by John B. Thompson; ritual of Aldo Natale Terrin.